Voluntary assisted dying : law? health? justice? (Australian National University Press, 2022)
Since the introduction of voluntary assisted dying, a 'new moment' in the governance of life and death has opened up within the Australian context. This new moment demands new questions be asked regarding the regime and its effects in this new era for law, health care and justice. This collection brings together critical perspectives on voluntary assisted dying itself, and on various practices adjacent to it, including questions of state power, population ageing, the differential treatment of human and non-human animals at the time of death, the management of health care processes through silent 'workarounds', and the financialisation of death. This book provides an overview of the first Australian regime, and then introduces these diverse critical views, broadening our engagement with euthanasia and voluntary assisted dying beyond the limited, but important, debates about law reform and its particular enactment in Australia. - Publisher's website.